(untitled) - Rue, Leslie W. (New York, 2001)
Business Management: Real-World Applications and Connections gives students an understanding of the way business works. It develops their technical knowledge and competence. Classroom experience is enhanced through a blend of text, visual presentation, and interactive resources.
Keywords: Business Administration,Quản trị kinh doanh